Mechanical properties of knitted kenaf fiber reinforced polyoxymethylene (pom) laminate composite - Dan-mallam, Y. (Microscopy Society of Malaysia, 2013)
The demand for natural fibers as reinforcing materials in polymer composites cannot be over emphasized due to low cost, light weight and relatevely easy fabrication.. Most natural fibers come in the short fiber form while some are twisted to form yarn. The distribution of the fibers in polymer matrix is a key factor in determining the mechanical properties of composites. One of the technique employed to achieve good mechanical properties is knitting of the fibers to achieve balanced mechanical properties. The main objective of this paper is to study the mechanical properties of knitted kenaf fiber composite in comparison to unidirectional kenaf fiber composite. A tensile strength of 85 MPa in both longitudinal and transverse directions (isotropic 2D) showed a balanced distribution of stress in the composite compared to 140 MPa for the unidirectional composite along the longitudinal direction. A flexural strength of 191.3 MPa showed a significant improvement compared to 82.1 MPa obtained for the unidirectional composite. The knitted kenaf composite showed low moisture uptake compared to the unidirectional composite. The low moisture uptake of the knitted kenaf composite will make it suitable for outdoor applications with high resistance to environmental degradation. Â© 2019, Microscopy Society of Malaysia. All rights reserved.